Comparative Efficacy and Safety of Poly (ADP-Ribose) Polymerase Inhibitors in Patients With Ovarian Cancer: A Systematic Review and Network Meta-Analysis - Luo, Jing; Ou, Shunlong; Wei, Hua; Qin, Xiaoli; Jiang, Qian (Frontiers in Oncology, 2022)
Objective: To compare the efficacy and safety of different PARP inhibitors in patients with ovarian cancer through a network meta-analysis and support clinical treatment choice. Methods: The Cochrane Library, PubMed, Embase, Science Citation Index, China National Knowledge Infrastructure (CNKI), Wanfang Data, Chongqing VIP (CQVIP) and Chinese BioMedical Literature Database (CBM) were searched with a cutoff date of Jan 14th 2021. ClinicalTrials.gov was also checked for supplementary data. Phase II or III randomized controlled trials that compared a PARP inhibitor with placebo in patients with relapsed or newly diagnosed advanced ovarian cancer were included. The hazard ratios (HRs) for progression-free survival and overall survival, and odd ratios (ORs) for grade 3 or higher adverse events were analyzed. The network meta-analysis was conducted in a bayesian framework basing on Markov Chain Monte Carlo model in R gemtc package (version 4.0.3). Results: Eight eligible articles reporting six trials with a total of 2801 patients were incorporated in this network meta-analysis. Three trials compared olaparib with placebo. Two trials compared niraparib with placebo. One trial compared rucaparib with placebo. The network meta-analysis failed to show significant differences in progression-free survival among the three PARP inhibitors: HR 0.64, 95% confidence interval 0.3 to 1.42 for olaparib versus niraparib, and olaparib versus rucaparib (0.86, 0.33 to 2.33). The comparison between niraparib and rucaparib also did not express statistically difference (1.34, 0.47 to 3.72). Subgroup analysis by BRCA gene status showed that no obvious difference in progression-free survival among the three PARP inhibitors regardless of BRCA mutation status. Olaparib had less grade 3 or higher adverse events than niraparib (OR 0.27, 95% confidence interval 0.13 to 0.55) and rucaparib (0.34, 0.14 to 0.86). But the analysis failed to show a significant difference between niraparib and rucaparib (1.27, 0.49 to 3.27).